Impact of Frontline demonstrations on Mungbean (Vigna radiata) productivity and profitability in Nagaur district of Rajasthan - H.R. Choudhary; Gopichand Singh; S.K. Bairwa; Bhawana Sharma (Annals of Agricultural Research, 2024)
Among the pulses, mungbean is one of the major crops. This crop is essential for boosting farmer income and achieving self-sufficiency in pulse production. The cluster frontline demonstrations (CFLDs) on Mungbean was conducted by Krishi Vigyan Kendra, Athiyasan, Nagaur-I at Dhehari (Tehsil Jayal), Roon and Indokali (Tehsil Mundwa) villages of Nagaur district during the Kharif season of 2020 to 2022. With the active participation of farmers, all 125 Mungbean crop demonstrations were conducted over 50 ha area with the goal of showcasing enhanced technology intended to prove the crop’s production potential. The result of the FLDs conducted by KVK shows a positive influence on farmer’s livelihood due to significant increase in average yield (10.34 q/ha) over local check (8.32 q/ha) with average 23.05% increased yield. The benefits-cost ratio was shown higher under demonstration (3.62) compared to the local check (2.92). The results showed that the adoption of improved variety with full package of practices increased Mungbean productivity with a significant reduction in extension and technology gap.